Dietary supplements for health, adaptation, and recovery in athletes - Rawson, E. S.; Miles, M. P.; Larson-Meyer, D. E. (International Journal of Sport Nutrition and Exercise Metabolism, 2018)
Some dietary supplements are recommended to athletes based on data that supports improved exercise performance. Other dietary supplements are not ergogenic per se, but may improve health, adaptation to exercise, or recovery from injury, and so could help athletes to train and/or compete more effectively. In this review, we describe several dietary supplements that may improve health, exercise adaptation, or recovery. Creatine monohydrate may improve recovery from and adaptation to intense training, recovery from periods of injury with extreme inactivity, cognitive processing, and reduce severity of or enhance recovery from mild traumatic brain injury (mTBI). Omega 3-fatty acid supplementation may also reduce severity of or enhance recovery from mTBI. Replenishment of vitamin D insufficiency or deficiency will likely improve some aspects of immune, bone, and muscle health. Probiotic supplementation can reduce the incidence, duration, and severity of upper respiratory tract infection, which may indirectly improve training or competitive performance. Preliminary data show that gelatin and/or collagen may improve connective tissue health. Some anti-inflammatory supplements, such as curcumin or tart cherry juice, may reduce inflammation and possibly delayed onset muscle soreness (DOMS). Beta-hydroxy beta-methylbutyrate (HMB) does not consistently increase strength and/or lean mass or reduce markers of muscle damage, but more research on recovery from injury that includes periods of extreme inactivity is needed. Several dietary supplements, including creatine monohydrate, omega 3-fatty acids, vitamin D, probiotics, gelatin, and curcumin/tart cherry juice could help athletes train and/or compete more effectively. Abstract from author